Draft Genome Sequence of the Cellulolytic and Xylanolytic Thermophile Clostridium clariflavum Strain 4-2a - Rooney, Elise A. (Genome Announc, 2015)
Clostridium clariflavum strain 4-2a, a novel strain isolated from a thermophilic biocompost pile, has demonstrated an extensive capability to utilize both cellulose and hemicellulose under thermophilic anaerobic conditions. Here, we report the draft genome of this strain.